2014
DOI: 10.1515/ehs-2013-0025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Energy Harvesting from ZnO Nanorods Using Different Flexible Substrates

Abstract: Abstract:The step toward the fabrication of nanodevices with low cost and improved performance is of high demand; therefore, in the present study, different flexible substrates like common paper, textile fabric, plastic and aluminum foil have been utilized to harvest electrical energy. ZnO nanorods (NRs) were grown by using low temperature aqueous chemical growth method. The obtained ZnO NRs were highly dense, well aligned, uniformly distributed over the substrates and exhibited good crystal quality. The struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, the density and the alignment of the NWs could be improved with the larger crystal size of the seed layer as shown in the two-dimensional (2D) AFM images of the surfaces of different seed layers (Figure 7a–c). It was reported that the alignment and density are essential morphological characteristics of the NWs, and these characteristics have a crucial role in the properties of the NW-based devices [46,49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the density and the alignment of the NWs could be improved with the larger crystal size of the seed layer as shown in the two-dimensional (2D) AFM images of the surfaces of different seed layers (Figure 7a–c). It was reported that the alignment and density are essential morphological characteristics of the NWs, and these characteristics have a crucial role in the properties of the NW-based devices [46,49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the PLZT-based materials are photoactive and can be used not only to harvest vibration energy (like other piezoelectric materials) but also can be used to harvest light and thermal energy. Other wide band materials such as zinc oxide have also been used for thermal energy harvesting (Zhao et al 2014;Hussain et al 2014;Feldhoff and Geppert 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To prepare the desired ZnO NSs, there exist many approaches including low and high temperatures [13, 14]. The relatively low temperature (< 100°C) aqueous chemical growth (ACG) method is better than other methods because a very low growth temperature is more suitable for soft/foldable substrates such as common paper, textile fabrics, flexible plastic and aluminium foil [15]. Furthermore, this method is relatively simple to adopt and of low cost, therefore it can also be used in bulk production.…”
Section: Introductionmentioning
confidence: 99%